The confidence code for girls : taking risks, messing up, & becoming your amazingly imperfect totally powerful self - Kay, Katty; Shipman, Claire, 1962-; Riley, JillEllyn (Harper, 2018)
Presents a collection of graphic novel strips, quizzes, lists, and stories providing girls with tips and strategies for bolstering their confidence. Encourages readers to challenge themselves and try the things they've always wanted to but are too afraid to.